The Utilizing of Microsite through S.id Platform as a Digital School Administration Portal for SMPN 01 Duhiadaa - Muh Wahyuddin S. Adam; Abdul Yunus Labolo (Universitas Muhammadiyah Enrekang, 2025)
This study aims to identify the use of the S.id microsite platform as a digital portal for teachers and education personnel in school administration at SMPN 01 Duhiadaa. The method used is a mixed method with a sequential exploratory design, combining qualitative (observation, interview) and quantitative (satisfaction survey) approaches. The development of the training program refers to the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The results of the study show that before the training, most teachers were not familiar with S.id platform. After participating in the workshop, participants were able to create an account, shorten the URL, adjust the appearance of the microsite, and produce digital products such as curriculum vitae, learning tools, and administrative tools. The survey data showed that 100% of respondents rated the interface access and interface to be easy to use, more than 70% rated the speed and administrative features as needed, 73% were satisfied, and 27% were very satisfied, while 91% rated the technical support adequate. These findings confirm that the use of microsites S.id effectively support the transformation of school administration towards an efficient and user-friendly digital system. ADDIE-based training programs have proven to be relevant to improve educators' technology skills while encouraging the creation of modern and sustainable school information management.